Analysing data using R: An application in healthcare sector - Tufail, Shahid; Abdul Qadeer, M (International Journal of Computer Sciences and Engineering, 2025)
With the advances in technology, data has too accumulated at an alarming pace and with that the need to analyze data has also grown. Facebook, Instagram, Twitter and other social networks have catalyzed the process of data accumulation. Data related to healthcare system is also growing with the growing incidences of cancer, diabetes and other diseases and the parallel advent of high-throughput technologies. In this paper, we have taken data from healthcare sector and analyzed them to accumulate knowledge of how the health condition of female diabetic patients and female non-diabetic patients varies according to various parameters such as age, blood pressure, skin thickness, and body mass index (BMI) and so forth.